Plotting a Socially Responsible Course for Computers Using Cybersecurity as an Example. - DeBenedictis, Erik P. (Computer (00189162), 2017)
Moore’s law drove an information revolution that changed the world. But computers will need more than raw performance in the future. Because computers now act as agents for humans, new issues arise that can only be addressed if engineers coordinate with lawyers and businesspeople.